The Whole Language Approach to Teaching French: An Effective Method for Developing Communicative Competence at the Primary Level. - Hyodo, Ann Mary (My University, 1990)
The approaches used in teaching French as a Second Language (FSL)
have changed over the years. The emphasis went from looking at the
individual elements of the language, like phonics or grammar, to the uses
of the language in the real world. The users of this language must be
able to demonstrate communicative competence, which is now the goal of any
FSL class. Scholars like Krashen feel that a language must be learned in
as natural a way as possible. When children learn their mother tongue,
they are not restricted by formal grammar lessons, nor are they limited
to daily vocabulary exposure. They are allowed to pursue their interests
and develop their language skills in their own way.
The Whole Language Approach is being advocated by the Hamilton Board of Education for all students. Since this approach is similar to the natural way to learn a language, it is a good way to develop communicative skills in the students.
In the French immersion class there is a great concern about the quality of French being produced by the students. OISE has recommended several strategies to eliminate the weaknesses shown by the testing.
Through the use of the Whole Language Approach many of these recommendations can be accommodated. A sample unit is included to show how the Whole Language Approach develops language and thinking skills in the children. They are encouraged to share their ideas and show their enthusiasm for learning. The classroom thus becomes an environment where meaningful learning experiences take place. Children want to interact with others. Therefore, this project shows that the Whole Language Approach can be an effective way to develop the communicative competence of the French immersion students.
Keywords: teaching; French and Francophone Language and Literature; French and Francophone Language and Literature